Study of the digestive tract of a rare species of Iranian blind cave fish (Iranocypris typhlops) - ALI EBRAHIMI (Biodiversitas Journal of Biological Diversity, 2015)
Ebrahimi A. 2015. Study of the digestive tract of a rare species of Iranian blind cave fish (Iranocypris typhlops). Biodiversitas 16: 173-178. The Iranian blind cave fish (Iranocypris typhlops) is a unique taxon which only lives within a cave in Lorestan Province insouthwest of Iran. Regardless of its enormous genetic interest, this species faces an imminent risk of extinction as no conservationefforts have been done for its protection. This study aimed to analyze the morphology of the digestive tract of this interesting fish using ahistological approach. Detailed examinations of the fishes showed that the mouth is horseshoe-shaped and located in an inferior situation(ventral side) of the head. In it, there are three rows of pharyngeal teeth including inner, middle and outer rows, which bear 5, 3 and 3 teethrespectively. The esophagus is very short and lined with an epithelium containing numerous mucous folds. The stomach is not present.The anterior segment of the intestine is S-shaped which comprises about one half the gut. In this part, there are mucosal folds which showdifferent sizes and mucous layer is thicker than other layers (submucosa, muscle layer and serosa). The distal portion of the intestine isstraight (rectal) and terminates to the anal region. In general, the ratio of intestine length is 1.2, as compared to the body length. Thisstudy showed that the liver in this taxon is composed of two lobes, the right lobe being two-parts and bigger than the left one. The gallbladder is clear and spherical in appearance. The pancreas is red or orange and observed as scattered masses of cells on the mesentery of thedigestive system. To our best knowledge, this is the first study to analyze the morphological characteristics of the digestive tract of theIranian blind cave fish, and its unique characteristics here found confirmed its singularity and so, the urgent need for its conservation.